STRATEGI PENINGKATAN KUALITAS PEMBINAAN KEMANDIRIAN PETERNAKAN DI LAPAS KELAS IIA BOGOR - Prasetyo, M. Gandhi; Yuska, Syahrial (Universitas Nusa Cendana, 2024)
This research discusses Quality Improvement Strategies in Animal Husbandry-based Independence Development at the Class IIA Bogor Correctional Institution. Implementation of duties and functions cannot be separated from the development process following procedures. In this case, livestock development, which is the flagship program of the Bogor Class IIA Correctional Institution, is the leading pioneer. From this, researchers are interested in reviewing the implementation of strategies on how to improve quality and what obstacles are faced in implementing coaching. In this research, the author uses the theory strategy presented by Bergman & Klefjso. Researchers used the Qualitative Descriptive method. The results of the analysis found that after conducting research 3 officers, Class IIA Sukabumi Prison, livestock-based independence development which is still not by applicable procedures, the obstacle faced is that the management of harvests at Bogor Class IIA Prison is still not following the management's expectations. Keywords: Quality Improvement Strategies; Animal Husbandry; Correctional Institution